The Price of Free Music: Valuation and Evaluation Processes in Pay-What-You-Want-Services - Lev Kalinichenko (Journal of Economic Sociology, 2015)
This study addresses the phenomenon of Pay-What-You-Want (PWYW) payment systems in relation to the distribution of digital music online. The processes of (e)valuation of items in these situations and the price formation are examined using examples of various cases of payment.The main goal of this study is to examine evaluation practices and discover motives of the buyer regarding digital music records under conditions of a PWYW-system. To examine this situation, a series of deep semi-structured interviews were conducted with payers about their practices of assigning worth, valuation during payments. The processes of categorization and legitimation were analyzed and the features of several justifications as well as the practices of its construction through categorization processes were distinguished.As a result of the study, a two-part character of the legitimation of payment is clearly discerned. Firstly, a person must appreciate the music which is recorded in those digital files, and secondly, the intention of supporting a musician is crucial for payment to happen. At the same time occasional appearances of other incentives were detected. Among them are payment as stimulation for production of new music and the advantages of a digital music file. Operating simultaneously, these motives make a heterarchy of incentives to pay for a piece of music in PWYW systems. In many cases a person pays not for the music file, but for various personal experiences, an artist’s work and other things surrounding and related to the music.To conclude, this study suggests a number of issues in economic life worth considering. Among those are: decision-making in a free pricing situation; to what extent rationality is behind these actions; what can be valued and priced; and finally the concept of a “sociological human” in contrast to an “economic human”. This study also suggests the possible benefits to specific musicians who might use PWYW, who might not be very popular but have having strong ties with their audience.